2016
DOI: 10.3109/13880209.2016.1149494
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect ofApodytes dimidiataon cisplatin-induced nephrotoxicity in Wistar rats

Abstract: Context Nutraceuticals possessing antioxidant potential have been used to alleviate side effects exerted by many chemotherapeutics, including cisplatin. Since Apodytes dimidiata E. Mey. Ex Arn. (Icacinaceae) shows antioxidant potential, it may possess significant chemoprotective effects. Objectives The study investigated whether A. dimidiata could attenuate cisplatin-induced renal damage. Materials and methods Nephrotoxicity was induced by cisplatin (single i.p., 16 mg/kg b wt.) in Wistar rats. Methanolic leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Experimental and clinical trials have shown that AMF does not alter the antitumor activity of chemotherapy or radiotherapy. AMF is currently recommended for the prevention of cisplatin-induced nephrotoxicity [39][40][41]. In this study, we used AMF and SAC to treat cisplatin-induced AKI were effective in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…Experimental and clinical trials have shown that AMF does not alter the antitumor activity of chemotherapy or radiotherapy. AMF is currently recommended for the prevention of cisplatin-induced nephrotoxicity [39][40][41]. In this study, we used AMF and SAC to treat cisplatin-induced AKI were effective in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…The development of renal tubule injury is caused by the oxidative stress induced by cisplatin [912]. The reactive oxygen species (ROS) and reactive nitrogen species (RNS) production [13] alter the structure and function of cellular membranes [14]. In addition to their accumulation in kidney and lysosomes [15] explained the mechanisms for CP-induced acute nephropathy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of whole-plant extracts and/or isolated fractions that contain more than one bioactive compound might be a better approach to cancer therapy due to the additive effect of single agents. In line with this thinking, plant extracts have been proposed as promising adjuvants for chemotherapeutic drugs in order to enhance their effectiveness [3,4] as well as to improve its cytotoxicity on healthy tissue [5,6].…”
Section: Introductionmentioning
confidence: 99%